Josephson dynamics and Shapiro steps at high transmissions: current bias regime - Galaktionov, Artem V.; Zaikin, Andrei D. (Beilstein Journal of Nanotechnology, 2024)
We investigate Josephson dynamics of highly transparent superconducting nanojunctions at subgap voltages and temperatures. In this limit, intrinsic dissipation in such junctions turns out to be sub-Ohmic, which yields a linear dependence of the average voltage on the bias current I slightly exceeding the critical one Ic. We demonstrate a strong impact of intrinsic sub-Ohmic dissipation on integer Shapiro steps appearing on the I–V curve in the presence of external microwave radiation.
Keywords: dissipation; Josephson effect; Shapiro steps; superconducting junctions